(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to investigate the effectiveness of digital environmental education in developing sustainability culture among university youth through a field study conducted on students of the Faculty of Engineering at the University of Tripoli. The study adopted a quantitative descriptive-correlational approach and used a questionnaire consisting of 20 items distributed across two main variables: Digital Environmental Education and Sustainability Culture. The study sample consisted of 421 students. The findings revealed a high level of digital environmental education among students, with an overall mean score of 4.07, while sustainability culture achieved a relatively high mean score of 3.58. The results also indicated a statistically significant positive correlation between digital environmental education and sustainability culture, suggesting that increased interaction with digital media and environmental online content contributes to enhancing sustainable behaviors and practices among students. The study further revealed a relative gap between digital environmental awareness and the actual practice of sustainable behaviors. In addition, significant differences were found according to academic year in favor of senior students, while no significant differences were attributed to gender. The study recommended strengthening digital environmental education within universities, developing interactive digital environmental content, and supporting digital environmental initiatives that contribute to promoting sustainability culture among university youth.